Gurbanskaya A. I. Cultural-historical and personal topics as literary reality and its manifestation in the works of G. Tyutyunnik - Gurbanskaya A. I (Philological Treatises, 2020)
In this article the question of belles-lettres cultural, historical and personal themes is highlighted, also its contents in “war” stories of Gr. Tutunnyk, created on the base of autobiography, is discovered.